2013
DOI: 10.1002/clen.201300032
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Methylene Blue on Transition Metals Doped SnO2 Nanoparticles

Abstract: Transition metals (M = Zn, Ni, Co, and Mn) doped stannic oxide MxSn1−xO2 at x = 0.1, 0.2, and 0.3 molar ratios have been successfully prepared. The results revealed that X‐ray diffraction peaks position exhibited the rutile tetragonal structure of cassiterite phase of SnO2 and there are no extra peaks of doped metal oxides at 0.1 and 0.2 molar ratio. However, secondary phase of doped metal oxides ZnO, NiO, Co3O4, and Mn2O3 were detected at 0.3 molar ratio. The average particles size of undoped SnO2 and doped s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…To date, a large number of scientific investigations about the photocatalytic degradation of aqueous organic pollutants, such as aliphatic alcohols, alkenes, phenols, dyes, and aromatic compounds have been reported [21][22][23][24]. In the present investigation, we focused our attention on the degradation of methylene blue (MB), which is usually used as a probe contaminant to evaluate the activity of the photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of scientific investigations about the photocatalytic degradation of aqueous organic pollutants, such as aliphatic alcohols, alkenes, phenols, dyes, and aromatic compounds have been reported [21][22][23][24]. In the present investigation, we focused our attention on the degradation of methylene blue (MB), which is usually used as a probe contaminant to evaluate the activity of the photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…These results were compared with the photocatalytic activity of ZnO and SnO 2 nanostructures obtained using other methods; the data included in the comparison are shown in Table 3. The catalyst concentration in our measurement was the lowest, yet not big difference in their activity [34][35][36][37]. The results of these measurements demonstrated that MO and MB dyes could be effectively degraded by the SnO 2 photo-catalyst nanoparticles, which were synthesized using pulsed plasma in liquid method, under irradiation of UV light.…”
Section: Sno 2 Nanoparticlesmentioning
confidence: 76%
“…Casados et al [4] show that pure tin oxide has photocatalytic properties similar to that of commercial titanium oxide (Degussa P25) under UV light irradiation in the degradation of methylene blue (MB) for reaction times in the range 0-1 h. However, due to the large band gap observed for SnO 2 , it can be photoactivated only by UV irradiation which constitutes only 4-5 % of the entire solar energy, leaving most of the visible portion of solar radiation. This limitation can be overcome by doping SnO 2 with transition metal ions such as Co, Ni, and Mn that extends the absorption spectrum from UV to visible regions, and therefore, the solar energy could be used effectively [8,9]. In addition to photocatalytic activity, inorganic metal oxides such as TiO 2 , ZnO, and SnO 2 doped with transition metal ions have received increasing attention in antimicrobial applications because such materials can achieve effective disinfection without the formation of any harmful by-products [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%